The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1590/s0001-37141999000400016
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity characteristics of filamentous fungi strains isolated from processed oat

Abstract: Nineteen strains of filamentous fungi isolated from processed oat were tested for pathogenicity factors, based on three parameters: growth at 37ºC, production of phospholipase and urease. Aspergillus niveus, Oidiodendron gryseum and Sporothrix cyanescens were positive for the three parameters. The other species were positive only for one or two of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…More recently, Q. cyanescens was found to be associated with cankers on C. calophylla and C. ficifolia in combination with Q. pitereka in Western Australia (Paap et al ., 2008); in that study pathogenicity trials confirmed that Q. cyanescens was non‐pathogenic to Corymbia spp. This fungus has also been identified from human skin and tissue samples (de Hoog & de Vries, 1973), as well as being associated with processed oats (Da Silva et al ., 1999). The presence of Q. cyanescens in both plantations and native spotted gum trees is of interest, but there currently appears to be no damage to tree health or wood quality.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Q. cyanescens was found to be associated with cankers on C. calophylla and C. ficifolia in combination with Q. pitereka in Western Australia (Paap et al ., 2008); in that study pathogenicity trials confirmed that Q. cyanescens was non‐pathogenic to Corymbia spp. This fungus has also been identified from human skin and tissue samples (de Hoog & de Vries, 1973), as well as being associated with processed oats (Da Silva et al ., 1999). The presence of Q. cyanescens in both plantations and native spotted gum trees is of interest, but there currently appears to be no damage to tree health or wood quality.…”
Section: Discussionmentioning
confidence: 99%
“…As culturas que apresentaram crescimento após o período de incubação foram consideradas como patogênicas (Silva et al, 1999;Neves et al, 2006).…”
Section: Crescimento a 37°cunclassified
“…Após esse período, um padrão de coloração vermelho -fuccina do meio indicava resultado positivo (Da Silva, 1999;Neves, 2006).…”
Section: Ureasesunclassified
“…Após esse período, um padrão de coloração vermelho -fuccina do meio indicava resultado positivo (Da Silva, 1999;Neves, 2006). Anni Kelle Serrão de Lima et al…”
Section: Ureasesunclassified